Creep and Recovery Behaviors of Lithium-Based Magnetorheological Grease - Ye, Xudan; Wang, Jiong (Frontiers in Materials, 2021)
This article studies the creep and recovery behavior of magnetorheological (MR) grease under constant stress shear. The experiment is done by using a parallel plate rheometer with magnetron attachment and temperature control unit.The effects of constant stress, CI particle concentration, magnetic field strength and temperature on creep and recovery behavior are systematically studied.Experimental results show that as the constant stress increases, the response strain will also increase.The creep strain tested under zero field is higher than the value tested under a magnetic field, indicating that the creep and recovery behavior of MR grease is highly dependent on the magnetic field strength. In addition, the creep and recovery behavior of MR grease is greatly affected by temperature. Under the action of a magnetic field, the creep strain will decrease with the increase of temperature. The result is opposite at zero magnetic field.